PENYULUHAN DAN EDUKASI STIMULASI MOTORIK KASAR DAN HALUS PADA PENDERITA STUNTING DI DESA MOJUPURNO MADIUN - Naftalia Rofiliana Devanti; Kristiyono Putro; Nungki Marlian Yulidarwati (Jurnal Pengabdian Masyarakat Multidisiplin, 2023)
Counseling is carried out to provide education to parents (mothers) about stunting such as signs of child symptoms indicating stunting and prevent stunting with adequate nutrition and train gross and fine motor stimulation independently at home. The method used in this counseling was in the form of health promotion regarding stunting in Mojopurno Village, Madiun Regency using poster media, giving pre-tests and post-tests in the form of questions to patients which are useful for measuring the effectiveness of counseling about stunting and providing training counseling carried out at home. Counseling ran smoothly and could be understood by parents (mothers) so that the results of the evaluation showed an increase in participants from 0% to 100% after the material was given. This activity can increase the knowledge of parents (mothers) in preventing stunting in children.